Taxonomy of the Tetramorium weitzeckeri species group (Hymenoptera: Formicidae) in the Afrotropical zoogeographical region - Garcia, Francisco Hita; Fischer, Georg; Peters, Marcell K. (Zootaxa, 2010)
The taxonomy of the Tetramorium weitzeckeri species group is revised for the Afrotropical zoogeographic region. The revision is based on morphology and morphometrics of the worker caste. Twenty six species are recognised of which twelve are described as new: Tetramorium bendai sp. n., Tetramorium boltoni sp. n., Tetramorium intermedium sp. n., Tetramorium kakamega sp. n., Tetramorium mkomazi sp. n., Tetramorium philippwagneri sp. n., Tetramorium renae. n., Tetramorium robertsoni sp. n., Tetramorium rubrum sp. n., Tetramorium susannae sp. n., Tetramorium tanaense sp. n., and Tetramorium trirugosum sp. n.. Tetramorium akengense (Wheeler, W.M. 1922) is revived from synonymy and Tetramorium tersum Santschi, Tetramorium (Xiphomyrmex) kivuense Stitz, and Xiphmyrmex kivuense st. atrinodis Santschi are proposed as junior synonyms of Tetramorium edouardi Forel. All other earlier synonymisations are confirmed here. The species group is redefined and subdivided into three species complexes which are defined and discussed: the Tetramorium edouardi complex (9 species), the Tetramorium muralti complex (8 species), and the Tetramorium weitzeckeri complex (9 species). An illustrated identification key to the Afrotropical species is presented, and for each species diagnosis, description, and taxonomic discussion are provided. Biogeography and important morphological characters of diagnostic value are discussed.